CAGIGAL EN LA HISTÓRIA DE LA EDUCACIÓN - J. Rodriguez (Asociación Española de Ciencias del Deporte, 2010)
Our work is an analysis of Cagigal's writings, trying to define the central themes of his educational theory through playing games. Finally these educational theories are illustrated through certain analogies with Homer, Pindarus, Plato, Rousseau, Pestalozzi, Fröbel, Coubertain, Maritain, Kirk and Groupe.